2014
DOI: 10.1107/s1399004714015053
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the 2,4′-dihydroxyacetophenone dioxygenase fromAlcaligenessp. 4HAP

Abstract: The enzyme 2,4 0 -dihydroxyacetophenone dioxygenase (DAD) catalyses the conversion of 2,4 0 -dihydroxyacetophenone to 4-hydroxybenzoic acid and formic acid with the incorporation of molecular oxygen. Whilst the vast majority of dioxygenases cleave within the aromatic ring of the substrate, DAD is very unusual in that it is involved in C-C bond cleavage in a substituent of the aromatic ring. There is evidence that the enzyme is a homotetramer of 20.3 kDa subunits, each containing nonhaem iron, and its sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 41 publications
(51 reference statements)
1
29
0
Order By: Relevance
“…[15] Initialb inding of the a-hydroxyk etone prior to dioxygen activationh as been proposed in the mechanism of the oxidative cleavager eaction by DAD. [16] For CYP17A1, [3,[17][18][19][20][21][22] an iron-peroxide speciesi si mplicated to initiatet he lyase reaction. Only very recently,t he proposed intermediate in the lyase step has been trappeda nd spectroscopically characterizeda sa ni ron-(III)-peroxo-hemiacetals pecies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Initialb inding of the a-hydroxyk etone prior to dioxygen activationh as been proposed in the mechanism of the oxidative cleavager eaction by DAD. [16] For CYP17A1, [3,[17][18][19][20][21][22] an iron-peroxide speciesi si mplicated to initiatet he lyase reaction. Only very recently,t he proposed intermediate in the lyase step has been trappeda nd spectroscopically characterizeda sa ni ron-(III)-peroxo-hemiacetals pecies.…”
mentioning
confidence: 99%
“…GC mass spectrao f: a) androstenedione,and of acetic acid formed in the reaction between 1 and 17a-hydroxyprogesteronewith b)16 O 2 and c)18 O 2 .Inset (c): molecularion peak for acetic acid at m/z 60 ( 16 O) and 62 ( 18 O).…”
mentioning
confidence: 99%
“…This substitution converts salicylic acid to catechol (Goyal & Zylstra, 1997;Bosch et al, 1999). Two genes, homogentisate 1,2-dioxygenase (PEM_03309) that are involved in the catabolism of aromatic rings (Borowski, Georgiev & Siegbahn, 2005), and 2, 4 dihydroxyacetophenonedioxygenase (PEM_00137), which helps in the cleavage of carbon-carbon bond in a substituent aromatic ring, were also detected (Keegan et al, 2014). The information mentioned above ratifies the capacity of Stenotrophomonas sp.…”
Section: Genetic Basis For the Degradation Of Pah By Stenotrophomonasmentioning
confidence: 68%
“…Use of the MATT-PROB server (Kantardjieff & Rupp, 2003) indicated that there were likely to be two molecules of DAD (which are approximately 20 kDa each) in the asymmetric unit. However, attempts at molecular replacement with various search models which had sequence homology to DAD failed to yield a solution, and when the structure of DAD was solved in a different crystal form (Beaven et al, 2014;Keegan et al, 2014) this also did not provide a convincing solution with the 1.1 Å resolution data set.…”
Section: Data Processingmentioning
confidence: 99%